Pengaruh Kebijakan Dividen dan Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024 - Fazria, Miftakhul; Rahayu, Heffi Christya; Anwar, Arfianti Novita (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to examine the effect of dividend policy and profitability on firm value in manufacturing companies within the food and beverage subsector listed on the Indonesia Stock Exchange during the 2020–2024 period, which covers both the COVID-19 pandemic and the post-pandemic recovery phase. This study aims to provide empirical evidence on how financial decisions and fundamental performance indicators influence market valuation under economic uncertainty. By focusing on a defensive industry, the research highlights the relative importance of dividend distribution and profitability in shaping investor perception. Materials and methods. This research employed a quantitative approach using secondary data derived from audited annual financial statements. The population consisted of 16 companies, and six firms were selected as samples through purposive sampling based on specific criteria, including consistent listing and dividend distribution during the observation period. Dividend policy was measured using Dividend Payout Ratio (DPR), profitability was proxied by Return on Equity (ROE), and firm value was measured using Price to Book Value (PBV). Data were analyzed using multiple linear regression with SPSS 21, following classical assumption tests. Results. The findings reveal that dividend policy has a positive and significant effect on firm value, although its impact is relatively modest. Profitability demonstrates a stronger positive and significant influence on firm value, indicating that investors place greater emphasis on fundamental performance. Simultaneously, dividend policy and profitability significantly affect firm value, with an adjusted R² of 0.698, suggesting substantial explanatory power. Conclusions. The study concludes that during periods of economic disruption and recovery, firm value in the food and beverage subsector is more sensitive to profitability than dividend policy. While dividend payments function as a positive market signal, sustainable earnings performance remains the primary driver of market valuation.